ERRORS 8th GRADE STUDENTS SOLVE STATISTICAL LITERACY: NEWMAN PERSPECTIVE - Naidatul Maghfiroh; Lydia Lia Prayitno (IAIN Ambon, 2023)
Statistical literacy is important for students because students will be exposed to their roles as producers and consumers of data. This study describes the errors of 8th-grade students in solving statistical literacy problems based on Newman's perspective. Two students of 8th-grade students at SMPN 6 Bondowoso who made the most errors were subjects in this study. This is a qualitative descriptive study through literacy problems, documentation, and interviews. The data were analyzed based on Newman's perspective and the guidelines for answering statistical literacy questions. The results showed that there were four errors in working on statistical literacy problems were (1) misunderstanding the problem, did not write down the information in the problems; (2) transformation error, the subject incorrectly the arithmetic operation used; (3) process skill error, the subject didn’t the calculation correctly. In addition, in this error the subject did not properly carry out the settlement procedure; and (4) errors in writing the final answer, the subject incorrectly write the final answer. The cause the subject makes errors is because they are not careful and do not understand the questions given. For this reason, teachers need to familiarize their students with solving statistical literacy problems. In addition, for students who have difficulty solving literacy problems, the teacher can provide scaffolding.